PENENTUAN SISWA BERPRESTASI KELAS BAHASA DI SMA “EFG” MENGGUNAKAN METODE EDAS - Andra Rizky Afandhi; Putri Aisyiyah Rakhma Devi; Harunur Rosyid (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
Achievement students are one of the references in the level of success in high school. Students who excel in the Language Class at SMA "EFG" Gresik Regency will receive an award in the form of financial assistance. In language classes at high schools throughout Gresik Regency, every year there will be outstanding students and these students will receive awards from the school. In determining high school students "EFG" so far only rely on student report cards and student test scores based on all subjects in the high school, which becomes an obstacle in determining outstanding students every year, for example if there are students who have high scores. can become outstanding students, even students who have special learning values ​​in the Language Department must become outstanding students. The EDAS method is used in determining student achievement by using predetermined criteria. Based on the final ranking calculation using the EDAS method, the results of the ranking of students who excel in language subjects at SMA "EFG" Gresik Regency are coded SW40 with an AS Final score of 0.50. The EDAS method only has an accuracy rate of 30% so that the results of the study show that only a few students can be categorized as outstanding students. The process of determining outstanding students in this study is not valid because the weight of the criteria used is less effective because it still needs to be added to the value of the weights on the criteria so that the use of the EDAS method in determining outstanding students will produce a higher level of accuracy.